Impact of Fossil Fuel Energy Consumption on CO2 Emissions: Evidence from Pakistan (1980-2010) (The Pakistan Development Review, 2014)
Global environmental problems are getting more attention especially the increase in earth temperatures and change in climate. Increase in world average air and ocean temperatures, widespread melting of snow and ice, and rising global average sea level are some evidences of global warming. A CO2 emission, which is a global pollutant is the main greenhouse gas that causes 58.8 percent of global warming and climate change [The World Bank (2007a)]. The intergovernmental panel on climate change (IPCC) reported a 1.1 to 6.4 °C rise in the world temperatures and an increase in the sea level of about 16.5 to 53.8 cm at the end of 21st century [IPCC (2007)]. Combined global land and ocean surface temperature for January 2010 on the average was 0.60°C (1.08°F) above the 20th century average of 12.0°C (53.6°F) and the average global temperature for January 2010 at the surface air was recorded 0.83°C (1.49°F) above the 20th century average of 2.8°C (37.0°F). Global warming is partly resulting from higher night temperature and partly due to rapid urbanisation. Other factors adding to global warming are the continuously changing irrigation systems, desertification and variations in the use of local lands. The developing countries need more energy consumption for economic growth that’s why these economies face more environmental issues.